WAKANISMO: MODEL OF ANDEAN THEORICAL APPROACH - Altamirano Enciso, Alfredo José (2015)
The word Huaca or Waka has changed its semantic dramatically between Quechua and Spanish languages caused by alienation of Spaniards conquerors since 1532 a.D. by intense acculturation and accentuation of Christianism. In Andean World the several social formations adapted to all ecological floors had a strong of ritual space and highly religiosity relationship to cult of Waka, phenomenon called Wakanism. It origin began to Late Archaic Period (3000-1800 b.C.) simultaneously to animal and plant domestication, development of ayni and minka, and settlement of several religious architecture traditions. To analyze this cultural phenomenon, we divided in five great categories: 1) the cult of Achachila, Auqui, Jirca and Huamani or Wamani, and others (Huamanism); 2) the cult of huacas concerns to several edified structures and sacred beings or gods; 3) the cult of huancas and puquios; 4) the cult of dead; 5) the cult of idols or fetiches. These autochthonous religious forms of Andean world have lived harmonically and permitted to develop of Andean civilizations